Review Jurnal: Nanokomposit Sebagai Penyerap Gelombang Elektromagnetik Untuk Radar Absorbent Material - Wulandari, Fira Putri; Nur, Aisyah Audrey; Gafira, Cahyani Elsa; Aritonang, Sovian (Rekayasa Material, Manufaktur dan Energi, 2024)
RAM or Radar Absorbent Material, is a substance designed to absorb radar or radio waves to prevent their reflection back toward the radar or enemy radar (Ishi et al. 2017). Extensive research has been conducted on RAM and its composition, particularly in the form of nanocomposites. To assess the effectiveness of a RAM's primary material, a key test is conducted to determine its electromagnetic wave absorption capability, known as the reflection loss test. This test quantifies a material's absorption ability, where a more negative reflection loss value indicates superior electromagnetic wave absorption. This literature review explores various nanocomposite materials and conductive polymers that can serve as the foundation for RAM. Notably, the PAni/Fe3O4 Nanocomposite emerges as the most efficient RAM material, boasting the lowest reflection loss at -53.7 dB.